Pelaksanaan Bantuan Modal Usaha Pemerintah pada Pelaku Usaha Mikro Kecil dan Menengah di Kelurahan Lolu Selatan Kota Palu - Bakarbessy, Maria Lea Frensy; M, Rudin.; Paerunan, Tris (Transpublika Publisher, 2025)
This study aims to analyze the implementation of Government Business Capital Assistance for Micro, Small, and Medium Enterprises (MSMEs) in South Lolu Village, Palu City, Central Sulawesi Province. Using a qualitative approach, four informants were selected, and data were collected through observation, interviews, and documentation. Data analysis followed the stages of data collection, reduction, presentation, verification, and conclusion. The research applies Tulus Tambunan’s framework, which assesses MSME capital assistance through four indicators: human resources, promotion, marketing, and business development. The findings indicate that the Government Business Capital Assistance program has generally been implemented well. However, in terms of human resources, the program has not been optimal due to limited competencies among MSME actors. In contrast, promotion efforts have been effective, supported by various government initiatives. The main inhibiting factors for MSME development include inadequate human resource skills, insufficient business capital, limited promotional activities, and challenges in securing bank loans. Conversely, supporting factors include government attention in the form of cash assistance, provision of production equipment, and marketing support through social media and exhibitions. Access to facilities such as mobile phones, online platforms (Zoom, YouTube, Google), and print media also significantly enhances the promotion of MSME products. Overall, while the program has contributed positively to MSME development, strengthening human resource capacity and expanding access to capital remain essential to maximize its impact.